The Wadsworth anthology of drama - Worthen, William B. 1955- (Wadsworth Cengage Learning, 2011)
A book from Cengage Learning on "The Wadsworth Anthology of Drama, Brief Edition". The boldest and most distinguished introduction to drama available today, W.B. Worthen's pace-setting text continues to provide exciting plays usefully situated within their historical and cultural contexts. Based on the best-selling WADSWORTH ANTHOLOGY OF DRAMA, the Brief Edition provides many of the important elements of that anthology but in a more streamlined form